Relationship between Organization Culture, Empowerment and Conflict - Khan, Muhammad Muddassar; Rasli, Amran Mohamed (International Journal of Economics and Financial Issues, 2015)
Higher Education Institutions in Pakistan are consistently witnessing increased level of conflicts among employee. This increase significantly impact culture of the higher education Institutions. Culture is driving force for the organizations behavior. Literature indicated the importance of organization culture for reshaping employee work practices, provide empowerment. Organizations are becoming more culturally diverse, mainly because of their operations diversity. Empowerment may affect the performance of the employee. Current study aims to investigate the relationship of the conflicts and employee performance, mediating role of empowerment and moderating role of organization culture. A Random sample of 100 employees from Higher Education institutions was selected. Study used a likert scale questionnaire for the data collection. Result revealed that there is a negative relationship of the employee conflicts and employee performance and empowerment moderates the relationship while organization plays a moderating role. Study is useful for the HEI's top management to understand the factors that lower employee performance. Keywords: Higher Education Institution; Conflicts, empowerment; Organization culture JEL Classifications: M00